Pengaruh Environment, Social and Governance terhadap Kinerja Perusahaan IDX ESGL dengan Variabel Moderasi Transformasi Digital - Aushaf Indra Luhfhi, Gusti; Mulyati, Heti; Juwita Ermawati, Wita (IPB University, 2025)
The role of Environmental, Social, and Governance (ESG) in influencing company performance has become a central topic in many investment considerations today. However, in its development, ESG alone has not been sufficient to deliver a significant improvement. Therefore, Digital Transformation (DT) has begun to be utilized to enhance the effectiveness of ESG. This study aims to analyze the effect of ESG on the performance of companies listed in the Indonesia Stock Exchange Environmental, Social, and Governance Leaders Index (IDX ESGL), with digital transformation as a moderating variable. The sample consists of 45 companies that were consistently included in the IDX ESGL index over five evaluation periods from 2019 to 2023. Data analysis was conducted using descriptive statistics and panel data regression, with the aid of Microsoft Excel, Python, and EViews 13. The findings of this study indicate that ESG has a positive and significant impact on financial performance, as proxied by Return on Assets (ROA) and Return on Equity (ROE), as well as on firm value, as measured by Tobin’s Q (TQ). However, digital transformation (DT) as a moderating variable does not strengthen the effect of ESG on financial performance or firm value. Based on the panel data regression results, the best-fitting model for the analysis without moderation (ESG only) is the Random Effect Model (REM) for Model 1 (ROA), Model 2 (ROE), and Model 3 (Tobin’s Q). Meanwhile, for models with DT as a moderator, the best-fitting models are the Fixed Effect Model (FEM) for Model 4 (ROA) and Model 6 (Tobin’s Q), and REM for Model 5 (ROE).